A Feasibility Study of the Translation of Cognitive Behaviour Therapy for Psychosis into an Australian Adult Mental Health Clinical Setting. Issue 1 (3rd April 2020) - Beames, Lee; Strodl, Esben; Dark, Frances; Wilson, Jennifer; Sheridan, Judith; Kerswell, Nicholas
Abstract: There is evidence that Cognitive Behaviour Therapy for Psychosis (CBTp) is an effective intervention for reducing psychotic symptoms. The recently updated Royal Australian and New Zealand College of Psychiatrists clinical practice guidelines (RANZCP CPG) recommend CBTp for the therapeutic management of schizophrenia and related disorders. Translational research is required to examine how well CBTp can be applied into public mental health services. This feasibility study aimed to provide preliminary evidence on how acceptable, implementable, and adaptable individual or group CBTp may be within a public mental health service in Australia. Twenty-seven participants initially agreed to participate in the study with 16 participants being randomised to either group or individual therapy, 11 starting therapy and 7 completing therapy. The intervention involved approximately 20 h of manualised CBTp. Attendance was higher in the individual therapy. Subjective reports indicated that the therapy was acceptable to all completers. Participants who engaged in individual or group CBTp experienced a similar level of reduction in the severity of hallucinations and delusions. Individual CBTp may be a feasible, acceptable, and effective intervention to include in Australian public mental health services. A pilot trial is now required to provide further evidence for and guidance of how best to translate CBTp protocols to Australian mental health services.